CIVIL JUDICIARY SYSTEM IN JAPAN - HORIE, Yuki (Comparative Legilinguistics, 2013)
In this article it is written about the organization of Japanese court and the comparison with Polish judiciary system, then each Japanese court and the persons who are involved in the trial is also presented in detail. In Japan, five types of cases are dealt with at the courts according to the Japanese law: civil case, administrative case, criminal case, family case and the case which is related with the juvenile. The last part of this article was devoted to about the civil case in Japan, especially about the overview of the civil procedure, naming of the parties and the important terms concerning the civil case.